2015
DOI: 10.4155/fmc.15.71
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase Ix Inhibitors in Cancer Therapy: An Update

Abstract: Carbonic anhydrases (CAs; EC 4.2.1.1) are well known zinc metalloproteins involved in the catalysis of a very simple but essential physiological reaction: carbon dioxide hydration to bicarbonate and proton. These enzymes are of clinical relevance in cancer therapy as among the 15 isoforms known in humans, two cell surface CA isoforms, namely CA IX (almost exclusively associated with tumors) and CA XII (overexpressed in some tumor types) are involved in tumorigenesis. Targeting the tumor associated isoforms IX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 36 publications
1
115
0
Order By: Relevance
“…CA9 is a powerful marker used to diagnose various types of metastatic cancers, including cervical, renal, breast and head, and neck tumors. Preclinical studies in cultured cells have clearly demonstrated that CA9 stimulates the metastatic properties of cancer cells . CA9 expression is increased in EC tissues and is correlated with poor prognosis and a malignant phenotype in patients with ESCC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA9 is a powerful marker used to diagnose various types of metastatic cancers, including cervical, renal, breast and head, and neck tumors. Preclinical studies in cultured cells have clearly demonstrated that CA9 stimulates the metastatic properties of cancer cells . CA9 expression is increased in EC tissues and is correlated with poor prognosis and a malignant phenotype in patients with ESCC .…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies in cultured cells have clearly demonstrated that CA9 stimulates the metastatic properties of cancer cells. 17,18,19 CA9 expression is increased in EC tissues and is correlated with poor prognosis and a malignant phenotype in patients with ESCC. 19 The current study detected increased CA9 expression in PADI4-overexpressing ECA109 cells and in PADI4-overexpressing mouse tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While the elevation in Ca14 was observed using the C-terminal tagged construct, the tag could not be detected, suggesting cleavage of the C-terminal region. CA9 has been an important target for pH modulation in several cancers including melanoma [45]. Melanosomal fractions from B16 cells did not contain CA14 ( Fig EV3G).…”
Section: Ca14 Is Localized To the Nucleus In Melanocytesmentioning
confidence: 97%
“…Carbon dioxide (CO 2 ) and its hydration product bicarbonate (HCO À 3 ) are substrates and products of various metabolic reactions in the cells of different living organisms [1][2][3][4][5][6][7] . CO 2 is the final product of the respiration in all domains of life, from microorganisms to mammals [8][9][10] ; bicarbonate (HCO À 3 ) is a substrate for several carboxylating enzymes involved in biosynthetic pathways such as biosynthesis of fatty acids, amino acids and nucleotides [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%